Impact of agroecology on soil fertility status and cassava yield in Nigeria: 1: nutrient levels in soils growing cassava - Asadu, C.; Nweke, F. (2000)
The soils of major cassava-growing areas of Nigeria were sampled at 0-20 and 20-40 depths in 1991. The objectives were to compare the nutrient levels in both cassava fields and other arable crop fields and relate their nutrient levels to possible factors that affect them. Approximately 470 samples (one half from each depth) were collected from the 65 villages covered in the study and analysed for 16 physico-chemical properties. Sand was the dominant particle size followed by clay in all the soils. Climate was the most important factor that related to the soil properties. The soils of the non-humid climate zone was the most fertile followed by those of the sub-humid zone. Soils grown to cassava and cassava mixtures were generally the same and also similar to those grown to other arables in most nutrients except total N which was higher in soils grown to cassava. Thus the soils grown to cassava were not marginal in terms of nutrient levels when compared to other arable fields even though the overall nutrient rating in all the soils was either low or medium for most of the nutrients. This suggests that relative to arable crops considered, including yam and maize, cassava was no longer grown in relatively poorer soils in the country.